Protein and Peptide Based Drug Delivery- A Review: Pharmaceutical Science-Biotechnology for Prospective Medical Science - P.V.Kamala Kumari; M.Yamini; Y.Srinivasa Rao; S. Satya Lakshmi (International Journal of Life Science and Pharma Research, 2022)
Biologics include vaccines, recombinant proteins, genes, synthetic tissues and viruses, which have emerged from molecular and cellular biology, with respect to unmet clinical needs and expanding indications. Hence it is important at this stage to outline the essential events that have led to the current level of interest in protein and peptide drug delivery systems. Polymers consisting of amino acids that are covalently linked by peptide bonds are known as Proteins and inturn peptides are small proteins composed of few dozen amino acids. Due to large molecular sizes of the proteins ranging from thousands to several millions atomic masses sizes; absorption through the epithelial barriers in the gastrointestinal tract is low. Moreover, proteins are rapidly degraded by digestive enzymes. As the bioavailability by oral route is poor they can be administered by other routes mainly by parenteral (IV, SC, IM) injections. The biological activity of proteins is strongly dependent on their molecular structure i.e 10 structure; the amino acid sequence, which ultimately dictates the non-covalent interactions and the 20i.e alpha helices and beta helices; the periodic spatial arrangement of the polypeptide chain backbone and 30; the 3-dimensional conformation of the whole molecule, including the positions of all amino acid side chains. Some proteins may consist of multiple peptide chains grouped together by non-covalent intermolecular interactions. The arrangement of these subunits relative to each other constitutes the 40structure. An alteration at any level of molecular structure leads to a change or loss of biological activity. The present review focuses on the development of various routes of drug administration, formulation as well as stability aspects of protein and peptide drug delivery system.